Structural features and assessment of prebiotic activity of refined arabinoxylooligosaccharides from wheat bran - Gullón, Beatriz (2014)
Wheat bran (WB) samples were subjected to two stage processing (aqueous extraction and hydrothermal treatment) to assess their potential as a raw material for the manufacture of xylan-derived prebiotics. The liquid phase from the second stage, containing hemicellulose- derived soluble arabinoxylooligosaccharides (AXOS), was refined by consecutive steps of membrane filtration and ion exchange. The purified AXOS were characterised by matrixassisted laser desorption/ionisation-time of flight mass spectrometry (MALDI-TOF-MS) and chromatographic techniques. The most complex saccharide identified was made up of 19 pentoses. Human faecal slurry cultures were used to assess the bifidogenic activity of AXOS and their effects on the production of Short Chain Fatty Acids (SCFA) and lactic acid. The results were compared with data obtained using fructooligosaccharides (FOS), which are accepted as the gold standard of a prebiotic ingredient. The stimulatory effects reached by AXOS upon the bifidobacterial population were of the same order as those obtained with FOS. Higher SCFA production was observed with AXOS in comparison with FOS.